The dimension disparity of upper jaw centralist insisivus and the nose size between Batak and Sundanese and the correlation - Sitepu, Rima Tea Kirana; Rodian, Mochammad; Djulaenahningsih, Djulaenahningsih (Universitas Padjadjaran, 2012)
Introduction: The disparity of tooth dimension and human organ between the race and the other one is determined by heredity. On the identification of dead victims of mass through the teeth have a high contribution in determining one’s identity. The study carried out to find out the dimension disparity of upper jaw centralist insisivus and the nose size between Batak and Sundanese and the correlation in a wide selection of programs in helping odontology forensic investigation of mass disasters. Methods: It is a comparative descriptive research. Total samples are 40, consisting of 20 Batak women (group 1) and 20 Sundanese women (group II) aged 18-30 years old. Result: The t-test result shows that p score of insisivus dimension is 11.21 and nose size of Batak and Sundanese about 0.000, 0.000, and 0.016. By correlation test of insisivus 11 and 21 with nose size of Batak, the correlation level is 0.851 and 0.925. The correlation test of insisivus 11 and 21 with the nose size of Sundanese, the correlation level is 0.947 and 0.949. Conclusion: There is a dimension disparity of upper jaw centralis insisivus and nose size between Batak and Sundanese and the correlation. It is in accordance with the statement that race shows the change of the human race because of the influence of the physical form of individuals, such as the shape and size of the teeth, which followed the growth in other parts of the body.